2017
DOI: 10.4997/jrcpe.2017.317
|View full text |Cite
|
Sign up to set email alerts
|

James Craufurd Gregory, 19Th Century Scottish Physicians, and the Link between Occupation as a Coal Miner and Lung Disease

Abstract: By the mid-19th century about 200,000 miners were employed in a UK coal mining industry still growing with the advances of the Industrial Revolution. Coal miners were long known to suffer poor health but the link to inhaling dust in the mines had not been made. In 1813 George Pearson was the rst to suggest that darkening of lungs seen in normal individuals as they aged was caused by inhaled soot from burning oil, candles and coal, which were the common domestic sources of heat and light. In 1831 Dr James Crauf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In fact, it turned out to be at odds with the observations he obtained later, regarding the impact of centrilobular emphysema on respiratory function in coal miners. 24 By 1968, 25 Gough was describing three kinds of centrilobular emphysema in his GWSs: (1) focal dust emphysema due to industrial dust-like coal; (2) soot emphysema caused by soot in atmospheric pollution in non-smokers of the general public; (3) Centrilobular Emphysema, due to bronchiolitis caused by exogenous agents such as smoking, infection, cadmium fumes, etc. With the benefit of hindsight, it is clear that Gough did not recognise the common feature of all three, namely the deposition of inhaled particles in the centrilobular region.…”
Section: The Pathogenesis and Aetiology Of Emphysema In Coal Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it turned out to be at odds with the observations he obtained later, regarding the impact of centrilobular emphysema on respiratory function in coal miners. 24 By 1968, 25 Gough was describing three kinds of centrilobular emphysema in his GWSs: (1) focal dust emphysema due to industrial dust-like coal; (2) soot emphysema caused by soot in atmospheric pollution in non-smokers of the general public; (3) Centrilobular Emphysema, due to bronchiolitis caused by exogenous agents such as smoking, infection, cadmium fumes, etc. With the benefit of hindsight, it is clear that Gough did not recognise the common feature of all three, namely the deposition of inhaled particles in the centrilobular region.…”
Section: The Pathogenesis and Aetiology Of Emphysema In Coal Workersmentioning
confidence: 99%
“…Lung disease in coal miners, known originally as miners’ phthisis or miners’ asthma, was first formally described in Edinburgh by Gregory in 1831, and its essential features were defined by the mid-nineteenth century. 1 However, in the late nineteenth and early twentieth century, before the advent of chest radiographs and based on the relatively good health of coal miners as opposed to urban dwellers and other miners, medical authorities judged the disease to have all but disappeared. Subsequently, some experts asserted that coal dust exposure was harmless, other than the effects of the quartz in it.…”
Section: The Recognition Of Coal Workers’ Pneumoconiosismentioning
confidence: 99%
“…17 With regard to the latter, Virchow had been sent preparations of coal miners' lungs by Swiss anatomist and histologist Rudolph Albert von Kolliker in the late 1850s, 18 who was at that time a guest of the anatomist, Dr John Goodsir and the surgeon Dr James Young Simpson, in Edinburgh. 17 By then, the midnineteenth century, Scottish physicians were advanced in their understanding of the role of the accumulated lung burden of coalmine dust in the development of disease in coalminer's lungs, 19 but Virchow remained unconvinced. In his paper on the pathology of coalminers' lungs in 1858, which described the preparations sent to him by von Kolliker and Goodsir, he wrongly concluded that it was 'extremely probable that we have here to do with pigmentary changes, resulting from extravasations of blood and the subsequent transformation of haematin, and not with an absorption and deposit of carbonaceous material inhaled into the lungs'.…”
Section: Resolution Of the Argumentmentioning
confidence: 99%
“…In his paper on the pathology of coalminers' lungs in 1858, which described the preparations sent to him by von Kolliker and Goodsir, he wrongly concluded that it was 'extremely probable that we have here to do with pigmentary changes, resulting from extravasations of blood and the subsequent transformation of haematin, and not with an absorption and deposit of carbonaceous material inhaled into the lungs'. 18 It was not until particles of charcoal were incontrovertibly identified by German physician Ludwig Traube in human lung specimens in 1860, on the basis of their morphology, 19 that Virchow fi nally stated in 1866, 50 years after Pearson's paper, that: 'Traube's well-known case fi rst convinced me that large fragments of vegetable coal can reach the alveoli and collect there … The very characteristic shape of charcoal completely excluded any possibility of error and from that moment I was convinced that there is a true pulmonary anthracosis'. 12 The entity of environmental anthracosis was generally accepted by 1916, when Canadian pathologist Oskar Klotz could fi nally write: 'Admitting that but few individuals today can escape the accumulation of carbon particles in the respiratory system, it may be suggested that the condition should be looked upon as a normal process'.…”
Section: Resolution Of the Argumentmentioning
confidence: 99%
“…These include the government, industry parties, and research institutes—predominantly from both Europe and the USA. Some of the major events from this timeline include the first pathological description of what we now know as coal workers’ pneumoconiosis (CWP) in 1831 (Donaldson et al, 2017 ) (Fig. 1 timepoint 1).…”
Section: Introductionmentioning
confidence: 99%